2020
DOI: 10.3389/fphys.2020.00112
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Fatigue in the Three Heads of Triceps Brachii During Intensity and Speed Variations of Triceps Push-Down Exercise

Abstract: The objective of this study was to investigate the effects of changes in exercise intensity and speed on the three heads of the triceps brachii (TB) during triceps push-down exercise until task failure. Twenty-five subjects performed triceps push-down exercise at three different intensities (30, 45, and 60% 1RM) and speeds (slow, medium, and fast) until failure, and surface electromyography (sEMG) signals were recorded from the lateral, long and medial heads of the TB. The endurance time (ET), number of repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 54 publications
2
10
0
1
Order By: Relevance
“…Similar findings have been reported for maximal isokinetic contractions performed at 60° s −1 , where the average sEMG initially increased and then decreased at fatigue 15 . Thus, there is evidence that during repeated dynamic contractions performed at controlled movement velocity, sEMG amplitude may initially increase and then decrease, while this phenomenon may be influenced by the resistive load 16 …”
Section: Introductionsupporting
confidence: 82%
“…Similar findings have been reported for maximal isokinetic contractions performed at 60° s −1 , where the average sEMG initially increased and then decreased at fatigue 15 . Thus, there is evidence that during repeated dynamic contractions performed at controlled movement velocity, sEMG amplitude may initially increase and then decrease, while this phenomenon may be influenced by the resistive load 16 …”
Section: Introductionsupporting
confidence: 82%
“…The scatter of data may be in uenced by limited number of torque values at low effort levels and be improved through the use of some digital dynamometer for exion task offering more sophisticated torque measurement. Further, the co-contractors might also have their part in the tasks performed [22]. Hence study of anthropometrics with co-contractors might also give some useful information.…”
Section: Discussionmentioning
confidence: 99%
“…The electrodes for the TB-Lat, and TB-Long were placed in accordance with the locations recommended by the Surface electromyography for the Non-Invasive Assessment of Muscles (SENIAM) [ 25 ]; the location of the electrode for the TB-Med was also in accordance with previous studies [ 8 , 26 28 ] ( Fig 2 ). For the TB-Med, ultrasonography was used to determine the superficial region of the muscle that faced the skin surface to minimize cross-talk ( Fig 3 ) [ 29 ] and followed the method of previous studies that measured the EMG signal of the TB-Med using a surface EMG electrode [ 21 , 28 ]. These previous studies used surface electrodes with a 2-cm interelectrode distance and found different EMG signal changes between the TB-Long and TB-Lat with muscle fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…The TB-Med is located at the deeper region, the fleshy origin is along the posterior humerus between the insertion of the teres major muscle and the olecranon fossa. The TB-Lat and TB-Long are located superficially, originating from the posterior surface of the superior humerus and infraglenoid tuberosity of the scapula, respectively, with two tendons at the proximal and distal ends [ 21 , 22 ]. All three heads of the TB insert by a common, broad tendon into the posterior surface of the olecranon and into the deep antebrachial fascia on each side of it [ 22 ].…”
Section: Introductionmentioning
confidence: 99%